Macro-Minerals Concentrations of Major Fodder Tree Leaves and Shrubs of District Chakwal, Pakistan - Ghazanfar, Shakira; Latif, Asma; Mirza, Imdad Hussain; Nadeem, Mukhtar Ahmad (Pakistan Journal of Nutrition, 2011)
The aim of present study was to find out the margin macro-mineral composition of 15 different fodder tree leaves and shrubs of district Chakwal of Pakistan. The climate of this region is characterized by a moderately low annual rainfall (350-500 mm.) Temperature during winter is 4-25°C and during summer is 15-40°C. Samples of fifteen tree leaves (Acacia nilotica, Acacia modesta, Albizzia lebbeck, Capparis decidua, Elaeagnus angustifolia, Grawia optiva, Gymnosporia royleana, Indigofera gerardiana, Morus alba, Prosopis cineraria, Panicum antidotale, Nerium odorum, Moringa oleifera, Ziziphus mauritiana and Zizyphus mummularia) were collected in march and April and analyzed for macro-minerals, i.e. Na (Sodium), K (Potassium), P (Phosphorus) and Ca (Calcium). The mean percentage values for Ca, P, Na, and K were 1.66, 0.26, 0.08 and 0.069, respectively. Our current investigations on nutritional evaluation of fodder tree leaves and shrubs revealed that these are good source of macro-minerals and can be used as substitute feed in the district of Chakwal, especially during the feed deficient periods.